Conflict Management Strategies for Character Building in Outstanding Wetland-Based Schools: A Case Study of Elementary Schools in North Banjarmasin - Suhaimi; Noorahim W; Ni'mah (Postgraduate, University of Mataram, 2025)
This study aims to examine the conflict management strategies employed by teachers in shaping students’ character at a high-performing elementary school located in a wetland area, specifically at a public elementary school in North Banjarmasin District. The research adopts a qualitative approach using a case study method. Data were collected through in-depth interviews, observations, and documentation, and were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings reveal three main strategies used by teachers in managing classroom conflicts: collaborative, compromising, and avoidance strategies. The collaborative strategy emerged as the dominant approach, as it fosters open communication and participatory problem-solving, which positively contributes to character development, particularly in the areas of responsibility, tolerance, and discipline. The compromising strategy is applied in addressing minor conflicts as a way to reach mutual agreements, while the avoidance strategy is used in certain situations to maintain classroom stability. These findings highlight that teachers’ skills in selecting and implementing appropriate conflict management strategies play a crucial role in supporting the success of character education, especially within the unique geographical and social challenges of wetland-based schools.